Introducing Aurora Kinase A as a Gene Target Against Photoaging: A Network Analysis: Aurora kinase A as a gene target against photoaging - Hossein-Khannazer, Nikoo; Arjmand, Babak; Asri, Nastaran; Razzaghi, Zahra; Razi, Farideh; Bandarian, Fatemeh; Robati, Reza M; Rezaei, Mitra; Ahmadzadeh, Alireza (Journal of Lasers in Medical Sciences, 2025)
Introduction: The solar radiation spectrum, which reaches the Earth’s surface, spans from infrared to ultraviolet. In the present study, human skin response to solar-stimulation radiation was assessed via directed protein-protein interaction (PPI) network analysis. Methods: Data were extracted from the Gene Expression Omnibus (GEO) database. The gene expression profiles of human skin after exposure to 100J/M2 versus the control were selected from GSE22083. The data were evaluated via box plot analysis and Uniform Manifold Approximation and Projection (UMAP) plot assessment. The differentially expressed genes (DEGs) were visualized via a Venn diagram. After cleaning the data, the queried DEGs were assessed via the directed PPI network by the application of the CluePedia plugin of Cytoscape software. The critical DEGs were pointed out based on out-degree value. Key actor genes were searched in GeneCards to find a suitable description of them. Results: Among 1482 significant DEGs, AURKA, CENPA, PP2R1B, UBE2O, RPA3, YKT6, SMARCA5, and SMAD3 were identified and highlighted as the critical actor genes in response to solar-stimulated radiation in human skin. Conclusion: AURKA appeared as the top-ranked DEGs in response to solar radiation in the human skin. Based on the findings, AURKA was pointed out as a suitable target against photoaging. The relationship between solar-stimulated radiation and photoaging, cancer promotion, innate immune system, DNA replication, repair of UV damage-induced, vesicular trafficking between the Golgi apparatus and the endoplasmic reticulum, exocytosis of neurotransmitter, exosome production, autophagy, maintenance of nucleosome spacing, and process of progressive fibrosis were established